The Roles of Intracellular Chaperone Proteins, Sigma Receptors, in Parkinson’s Disease (PD) and Major Depressive Disorder (MDD) - Yang, Kai; Wang, Changcai; Sun, Taolei (Frontiers in Pharmacology, 2019)
Sigma receptors, particularly the sigma-1 receptors, are highly expressed in the CNS. They are intracellular receptors, acting as chaperone proteins. Sigma receptors localize mainly at the mitochondrial-associated endoplasmic reticulum (ER) membrane (MAM). Upon stimulation, they translocate from MAM to plasma membrane (PM) and nucleus, where they interact with many proteins and ion channels. In recent years, significant progress has been made in our understanding of roles of the Sigma-1 receptors in normal and pathological conditions, but more studies are still required for the Sigma-2 receptor. The physiological roles of Sigma receptors in the CNS are discussed. They can modulate neuronal excitability, synaptic plasticity and learning and memory. Moreover, the activation of Sigma receptors protects neurons from death via several pathways. Evidences about the involvement of Sigma-1 receptors in Parkinson’s Disease (PD) and Major Depressive Disorder (MDD) are also presented, which indicating Sigma-1 receptors might be promising targets for pharmacologically treating PD and MDD.